Islamic Education and The Society Era 5.0 (Opportunities and Challenges for Islamic Education Institutions) - Muhammad Mukhlish Nasrulloh (Universitas Islam KH. Achmad Muzakki Syah Jember, 2026)
This study examines how Islamic education institutions respond to the socio-educational transformation of the Society 5.0 era, marked by the growing use of artificial intelligence, digital platforms, learning management systems, and online religious resources. While these technologies expand access to learning and support pedagogical innovation, they also raise concerns about digital literacy gaps, source validity, academic integrity, spiritual depth, and ethical governance. Using a qualitative interpretive case study design, this study explores the opportunities and challenges of Society 5.0 in Islamic education institutions. Data were collected through in-depth interviews, limited observation, and document analysis involving institutional leaders, Islamic Religious Education teachers, students, administrative staff, and technology or curriculum managers. The data were analyzed using reflexive thematic analysis. The findings identify four interconnected themes: digital learning expansion as pedagogical transformation, negotiation between technological convenience and spiritual formation, institutional readiness as the foundation of digital transformation, and digital adab as an ethical framework for human-centered AI. These themes show that Society 5.0 does not merely change learning tools, but reshapes teacher-student relations, knowledge authority, curriculum adaptation, institutional governance, and the ethical meaning of digital practice. The study contributes by proposing human-centered Islamic digital education as a conceptual perspective that places technology within the framework of Islamic values, academic honesty, moral responsibility, spirituality, and public benefit. Practically, the study recommends strengthening AI ethics guidelines, teacher digital competence, student critical literacy, equitable access, and value-based institutional governance to ensure that digital transformation supports both educational innovation and spiritual formation in contemporary Islamic education contexts.